Предмет: Алгебра,
автор: Apelsin5656
Как решить!!!
11/3 * ( 8/3 -2 ) - 8/3(8/3 -2)
Ответы
Автор ответа:
0
11/3 * (8/3-2)-8/3(8/3-2)=(8/3-2)*(11/3-8/3)=(8/3-2)*(3/3)=8/3 - 2 = 8/3 - 6/3 = 2/3
Автор ответа:
0
У вас разные ответы!!
Автор ответа:
0
= ( 8/3 - 2 ) * [ ( 11/3 ) - ( 8/3 ) ] = ( 8/3 - 2 ) * ( 3/3 ) = ( 8/3 ) - 2 = ( 8/3 ) - ( 6/3 ) =
= 2/3
ОТВЕТ 2/3
= 2/3
ОТВЕТ 2/3
Похожие вопросы
Предмет: Английский язык,
автор: kvigarkul385
Предмет: История,
автор: VikaAkulova
Предмет: Окружающий мир,
автор: Аноним
Предмет: Математика,
автор: junysha
Предмет: Геометрия,
автор: freehat